FACTORS RELATED TO THE PRESENCE OF AEDES SP. MOSQUITO LARVAE IN THE IMPLEMENTATION OF MOSQUITO NEST ERADICATION IN THE WORKING AREA OF THE KENALI BESAR COMMUNITY HEALTH CENTER IN JAMBI CITY IN 2026 - Muthiah Fauziyyah Syadiq; Oka Lesmana; Andree Aulia Rahmat; Rd. Halim (PT. Radja Intercontinental Publishing, 2026)
Dengue Hemorrhagic Fever remains a public health problem influenced by preventive behavior and home environmental conditions. This study aims to analyze factors related to the presence of Aedes sp. larvae in the implementation of PSN in the Kenali Besar Community Health Center, Jambi City, in 2026. This study is an observational analytic study with a cross-sectional design. The study population was all heads of families in the Kenali Besar Community Health Center, with a sample of 110 houses selected through simple random sampling. The research instruments were questionnaires, observation sheets, and hygrothermometers, while the data were analyzed using the chi-square test. The results showed a significant relationship between knowledge, attitudes, PSN actions, the role of health workers, and humidity with the presence of Aedes sp. larvae, while temperature was not significantly related. In conclusion, larva control is more related to behavioral factors and home microenvironment, so health education, strengthening jumantik cadres, and consistency of PSN need to be continuously strengthened